Proteomic Analysis of the Parasitic Cnidarian Ceratonova shasta (Cnidaria: Myxozoa) Reveals Diverse Roles of Actin in Motility and Spore Formation - Brekhman, Vera; Ofek-Lalzar, Maya; Atkinson, Stephen D.; Alama-Bermejo, Gema; Maor-Landaw, Keren; Malik, Assaf; Bartholomew, Jerri L.; Lotan, Tamar (Frontiers in Marine Science, 2021)
Myxozoans are widely distributed aquatic obligate endoparasites that were recently recognized as belonging within the phylum Cnidaria. They have complex life cycles with waterborne transmission stages: resistant, infectious spores that are unique to myxozoans. However, little is known about the processes that give rise to these transmission stages. To understand the molecular underpinnings of spore formation, we conducted proteomics on Ceratonova shasta, a highly pathogenic myxozoan that causes severe mortalities in wild and hatchery-reared salmonid fishes. We compared proteomic profiles between developmental stages from inside the fish host, and the mature myxospore, which is released into the water where it drifts passively, ready to infect the next host. We found that C. shasta contains 2,123 proteins; representing the first proteomic catalog of a myxozoan myxospore. Analysis of proteins differentially expressed between developing and mature spore stages uncovered processes that are active during spore formation. Our data highlight dynamic changes in the actin cytoskeleton, which provides myxozoan developmental stages with mobility through lamellipodia and filopodia, whereas in the mature myxospore the actin network supports F-actin stabilization that reinforces the transmission stage. These findings provide molecular insight into the myxozoan life cycle stages and, particularly, into the process of sporogenesis.